EFFECTS OF LASALOCID AND NITROGEN SOURCE ON DIGESTION AND NITROGEN BALANCE IN RAMS - González-Muñoza S. S.; J. M. Pinos-Rodríguezb; R. Lópeza; J.R. Bárcena-Gamaa; M. A. Cobos-Peraltaa; Y. López-Hernándezb (Journal of Animal and Plant Sciences, 2015)
Four Creole rams (57 ± 3.5 kg BW), fitted with ruminal cannulae, were used to evaluate the effects of lasalocid on digestion, ruminal kinetics and nitrogen balance using two diets with different nitrogen source e.g. blood meal and poultry litter. Dry matter intake was not affected by blood meal or poultry litter. Total tract digestion of organic matter, crude protein, neutral detergent fiber and acid detergent fiber was greater (P < 0.05) for poultry litter. Rams fed poultry litter excreted more (P < 0.001) urinary N than those receiving blood meal; therefore, the diet containing blood meal elicited a better N retention (P < 0.001). The poultry litter diet caused a larger (P < 0.05) ruminal degradation of dry matter, nitrogen and neutral detergent fiber, as well as ruminal ammonia-N concentration compared to the blood meal diet. Lasalocid decreased ruminal bacteria population, and as a consequence total tract digestion only in rams fed the blood meal diet (P < 0.05).
Keywords: ionophores; degradation; fermentation; nitrogen excretion